Cara de bandido: as representações sociais de criminosos para juristas e não juristas - Pompeu, Júlio César (2013)
The subject of this thesis was the social representations of criminals, especially those common to the field of social law professionals - judges, prosecutors and lawyers -. There were four empirical, parallel and non-linear - the data produced by one of them isn"t subsidized others -. The first survey investigate, through a form built with criminal sketches from which the participants should aim author and victims of crimes, if the appearance can interfere in criminal trials conducted by lawyers. The second consisted of content analysis of criminal science journal articles and reviews of crimes news on internet news portal. Third, content analysis of comments to news reporters two crimes - death of a baby and racial slur - unusual but highly publicized among readers of electronic news portals. The last, content analysis of monocratic civil and criminal decisions of Superior Court judges. For content analyzes were used traditional procedures (Bauer, 2012; Bardin, 2006) coupled with electronic resources - Alceste (Reinert, 1998) and MAXQDA (Kuckartz, 2007). The results show a direct relationship between ugliness, poverty, power and dangerous assignment. This indicates the existence of more than one representation of crime among jurists with "profiles" of criminals among different crimes and different consequences in criminal trials. These results help to better understand the processes of judicial prosecution.